Integrasi Antara Sifat Alami Manusia (fitrah) dan Terapi Perilaku Kognitif (CBT) dalam Praktik Konseling untuk Mendukung Remaja dalam Mengelola Konflik Identitas - Noor Ain binti Sukarno (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
: Identity conflict is a significant developmental issue among adolescents, particularly in the context of psychosocial challenges, social media influence, and value discrepancies between modern culture and religious beliefs. Inadequate management of identity conflict may result in emotional distress, role confusion, and maladaptive behaviors. This study aims to analyze the integration of the Islamic concept of fitrah and Cognitive Behavioral Therapy (CBT) in counseling practice as a holistic intervention for managing adolescent identity conflict. A qualitative literature review was conducted by examining contemporary Islamic psychology literature and empirical studies on CBT in adolescent counseling. The findings indicate that CBT is effective in addressing irrational thoughts and maladaptive behaviors, while fitrah reflects the innate human nature toward goodness, truth, and psychological balance. The integration of these approaches forms a holistic counseling framework encompassing cognitive, emotional, behavioral, and spiritual dimensions. This study concludes that the integrative fitrah–CBT approach has strong potential as a comprehensive counseling intervention for addressing adolescent identity conflict.